Kedudukan Menteri Sebagai Kader Partai Politik Dalam Sistem Presidensial Indonesia: Antara Loyalitas Partai dan Tanggung Jawab Konstitusional - Octavianingsih, Yetti; Abdillah, Rachmat; Rahayu, Indah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Abstract In the fundamental principles of presidentialism, ministers are aides to the president who must possess singular loyalty to the head of government. However, post-reform political practices have shown that ministerial appointments are often driven by the interests of political coalitions, leading to the phenomenon of dual loyalty between constitutional responsibilities and party affiliation. This issue is exacerbated by the oligarchic and transactional nature of Indonesian political parties. Ministerial appointments are frequently perceived as “political rewards” in the post-election power-sharing process, rather than as part of a technocratic strategy to achieve effective governance. Through a normative approach, this study examines legal provisions, constitutional principles, and public office ethics that are relevant, as well as their impact on governmental effectiveness, bureaucratic neutrality, and public policy accountability. The findings of this study highlight the need to strengthen ethical and legal regulations to restrict the holding of dual structural positions within political parties and executive office, in order to reinforce a democratic and accountable presidential system